Effect of carburizing via current heating technique on the near-surface microstructure of AISI 1020 steel - Boonruang C. (Chiang Mai University, 2015)
AISI 1020 steels with 1.8 cm diameter and 1.8 cm height were heat treated by heating at 950°C, quenching and then tempering at 650°C for 60 min. After that, they were ground with 1000 grid SiC paper and then polished with 0.3 mm alumina paste. The steels were carburized using the current heating technique with the applied electrical powers of 40-240 W for 20 min. The near-surface phases and microstructure of the steels were characterized using the optical microscope, scanning electron microscope, energy dispersive X-ray spectroscopy and X-ray diffractometer. The surface hardnesses of the steels were measured using microhardness tester. The fractions of pearlite at the surface of the carburized steels are high and they are decreased as the distance from the surface increased reflected the effect of carbon diffusion on the microstructure of the steel. However, the fraction of Fe 3C was not high enough to be detected by the XRD. Fe 2O 3 and Fe 3O 4 could be formed on the steel during the carburizing process. The hardness of the steel increased with increasing applied electrical power. The hardness of the steel carburized at 240 W is the highest which is 44.87% increased compared to the uncarburized steel.